El matrimonio en el Misterio de Cristo (Scripta Theologica, 2018)
Pope John Paul II in his address to Council of the General Secretariat of the Synod (23-2-80) points out, in the first place, that marriage is the first form of the family and that it is alliance and love, a sign of the alliance of Christ with his Church and a reflection of trinitarian love. He goes on to state that the family is an institution which transcends the will of the individual and the decisions of social bodies. He indicates finally that it is necessary to give particular attention to preparation for love and marriage.Some authors (Huxley, Cox, etc) speak of the unitary family as a by-product of the technological society and opine that this type of family has not been too successful. They conclude that the nuclear family, as they call it, is like any other human institution, neither sacred nor eternal. On the other hand, however, Vatican II teaches that the wellbeing of the person and of society depends to a great extent on the moral health of the family. And if the present-day situation presents not a few difficulties (GS 47), there is the historical evidence that the institution of the family has been able to survive all the crises of civilisation (GS 47).In ancient Israel the conception of family comes from being considered the essential cell al the clan, tribe, or people to being the place where the messianic hopes, the revelation and fidelity to the alliance are tought.Jesus teaches that the individual and the family are part of the Kingdom, that superior reality which gives consistency and meaning to everything. Jesus who was barn and lived in an ordinary family reveals to us that we belong to another family, to that of the Father who is in Heaven. This family is the only one which can ask for a total and unconditional dedication. The private family is not lost or dissolved in the universal. It is rather a reflection of the great universal family and is the learning ground for the behaviour which' should reign in it.The family has its basis in matrimony and this latter, which springs from the nature of man, is an original gift which comes from God. Natural and human sexuality is also a gift of God and the union of man and woman, willed by God, is in a certain sense sacred. The New Testament deepens in understanding this sacred character of matrimony and St. Paul states that marriage has to be "in the Lord". He describes it as a great mystery which reflects the love of Christ for men: marriage is a channel of the redeeming love of God manifested in his Son and the love by which the spouses love one another has its source in the love of Jesus himself.The Church distinguishes matrimony from other interhuman relationships and attributes to it a nature that is properly sacramental. Matrimony is a sacrament. It is an act of Christ realised in his Church which introduces the spouses into his paschal mystery and it is an image of the union of Christ and his Church. Christ himself forms part of the conjugal alliance and consecrates this interpersonal relationship.On account of the internal and dynamic character of baptismal lite, the matrimonial alliance of baptised persons cannot be separated from, Christ. It is an alliance "in the Lord”. Thus, if the baptised person wishes to be consequent with the demands of his faith, he must understand that there is no valid marriage for him other than the sacramental. The union is indissoluble since a sacred bond which is not subject to human decision arises from the mutual sell-giving (GS 48). And since the juridical institution to which matrimony leads comes from God, Creator and Redeemer, the approach of free love or the opinion that the institutional is irrelevant when true love is lacking, are shown to be meaningless.Conjugal love, although it is ordered to procreation, has substantial value in itself and not simply instrumental (GS 50). It is a love in Christ which implies a penetration of God in human life, with its bodily and spiritual elements: God sanctifies the whole love of the spouses. The mutual giving, when genuine, is praiseworthy, meritorious and sanctifying because the more love the spouses have for one another, the more they draw close to Christ, and the more they draw close to Christ, the more they are united to one another. All of the above explains what conjugal spirituality is, because God wants that the spouses love one another, that they, be fruitful and holy by sharing life in all its dimensions, in other words, that they live in communion and dialogue with each other.True conjugal lave is for "ever" and is also "total self-giving". One for the other and "for ever" are the indispensable conditions.But at the same time, the spouses "open" themselves to others. The first openness is to children through procreation and education. The life in Christ of each member of the family community transforms the christian home into a type of domestic church and also places the family in the broader context of the Kingdom of God. It makes a home be open to the universal Church and promotes the values of solidarity, cooperation, help and social apostolic commitment.